Anesthetic management of a patient with spinocerebellar degeneration - Prasanna Vadhanan; Pramod Kumar (Wolters Kluwer Medknow Publications, 2011)
Spinocerebellar degeneration or olivopontocerebellar degeneration denotes a group of disorders of various etiologies manifesting as degenerative changes of various part of the central nervous system. We describe the anesthetic management of a patient with severe olivopontocerebellar degeneration posted for vaginal hysterectomy. A combined spinal epidural technique was performed at the level of L2-L3. The anesthetic implications of the various aspects of spinocerebellar degeneration are discussed.